Writing from a Distance. The Past and the Present in Novels by Central and Eastern European Female Migrant Writers in Italy - Belozorovich, Anna (Poznańskie Studia Slawistyczne, 2019)
Based on a research concerning literary works by the authors from Central and Eastern European countries living in Italy, this article explores the imaginary bonded to a vast geographical area and to a variety of social experiences connected to that area under regime or to the post-migration condition. The interviews conducted with the selected writers allow the authoress to gather elements that show the perception of the place of origin and its connection with neighboring countries, suggested by different motivations. The literary works cited in the article give testimony of lives under regimes and describe moments of transition due to political and social change or to the choice to migrate. While revealing sometimes a stereotyped view of the idea of ‘East’ in opposition to the ‘West’, these different voices, located at a spatial and temporal distance from the social realities they explore, suggest an important role of literary expression as means for contrasting the oblivion of the past and present injustices.